(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The term ICU acquired infection refers to an infection that was not present during admission to the ICU, and that may occur after discharge from ICU. It is estimated that 10-25% of persons are affected by nosocomial infection in India each year. The nurses can play a major role in preventing the hospital acquired infections thorough knowledge regarding modes of spreading and control measures.